The differential binding of E2F and CDF repressor complexes contributes to the timing of cell cycle-regulated transcription. - Lucibello, F C (1997)
B- myb and cdc25C exemplify different groups of genes whose transcription is consecutively up-regulated during the cell cycle. Both promoters are controlled by transcriptional repression via modules consisting of an E2F binding site (E2FBS) or the related CDE plus a contiguous CHR co-repressor element. We now show that the B- myb repressor module, which is derepressed early (mid G1), is preferentially recognized by E2F-DP complexes and that a mutation selectively abolishing E2F binding impairs regulation. In contrast, the cdc25C repressor module, which is derepressed late (S/G2), interacts selectively with CDE-CHR binding factor-1 (CDF-1). E2F binding, but not CDF-1 binding, requires specific nucleotides flanking the E2FBS/CDE core, while CDF-1 binding, but not E2F binding, depends on specific nucleotides in the CHR. Swapping these nucleotides between the two promoters profoundly changes protein binding patterns and alters expression kinetics. Thus predominant CDF-1 binding leads to derepression in late S, predominant E2F binding results in up-regulation in late G1, while promoters binding both E2F and CDF-1 with high efficiency show intermediate kinetics. Our results support a model where the differential binding of E2F and CDF-1 repressor complexes contributes to the timing of promoter activity during the cell cycle.